Correlation between differential drought tolerability of two contrasting drought-responsive chickpea cultivars and differential expression of a subset of CaNAC genes under normal and dehydration conditions - Nguyen, Kien Huu; Ha, Chien Van; Watanabe, Yasuko; Tran, Uyen Thi; Nasr Esfahani, Maryam; Nguyen, Dong Van; Tran, Lam-Son Phan (Frontiers in Plant Science, 2015)
Drought causes detrimental effect to growth and productivity of many plants, including crops. NAC transcription factors (TFs) have been reported to play important role in drought tolerance. In this study, we assessed the expression profiles of 19 dehydration-responsive CaNAC genes in roots and leaves of two contrasting drought-responsive chickpea varieties treated with water (control) and dehydration to examine the correlation between the differential expression levels of the CaNACs and the differential drought tolerability of these two cultivars. Results of real-time quantitative PCR indicated a positive relationship between the number of dehydration-inducible and -repressible CaNAC genes and drought tolerability. The higher drought-tolerant capacity of ICL482 cultivar vs. Hashem cultivar might be, at least partly, attributed to the higher number of dehydration-inducible and lower number of dehydration-repressible CaNAC genes identified in both root and leaf tissues of ICL482 than in those of Hashem. In addition, our comparative expression analysis of the selected CaNACs in roots and leaves of ICL482 and Hashem cultivars revealed different dehydration-responsive expression patterns, indicating that CaNAC gene expression is tissue- and genotype-specific. Furthermore, the analysis suggested that the enhanced drought tolerance of ICL482 vs. Hashem might be associated with 5 genes, namely CaNAC02, 04, 05, 16 and 24. CaNAC16 could be a potential candidate contributing to the better drought tolerance of ICL482 vs. Hashem as a positive regulator. Conversely, CaNAC02 could be a potential negative regulator, contributing to the differential drought tolerability of these two cultivars. Thus, our results have also provided a solid foundation for selection of promising tissue-specific and/or dehydration-responsive CaNAC candidates for detailed in planta functional analyses, leading to development of transgenic chickpea varieties with improved productivity under drought.